Rat Urinary Osteopontin and Neutrophil Gelatinase-Associated Lipocalin Improve Certainty of Detecting Drug-Induced Kidney Injury. (28th March 2016) - Phillips, Jonathan A.; Holder, Daniel J.; Ennulat, Daniela; Gautier, Jean-Charles; Sauer, John-Michael; Yang, Yi; McDuffie, Eric; Sonee, Manisha; Gu, Yi-Zhong; Troth, Sean P.; Lynch, Karen; Hamlin, Diane; et al.
Abstract: Traditional kidney biomarkers are insensitive indicators of acute kidney injury, with meaningful changes occurring late in the course of injury. The aim of this work was to demonstrate the diagnostic potential of urinary osteopontin (OPN) and neutrophil gelatinase-associated lipocalin (NGAL) for drug-induced kidney injury (DIKI) in rats using data from a recent regulatory qualification submission of translational DIKI biomarkers and to compare performance of NGAL and OPN to five previously qualified DIKI urinary biomarkers. Data were compiled from 15 studies of 11 different pharmaceuticals contributed by Critical Path Institute's Predictive Safety Testing Consortium (PSTC) Nephrotoxicity Working Group (NWG). Rats were given doses known to cause DIKI or other target organ toxicity, and urinary levels of the candidate biomarkers were assessed relative to kidney histopathology and serum creatinine (sCr) and blood urea nitrogen (BUN). OPN and NGAL outperformed sCr and BUN in identifying DIKI manifested as renal tubular epithelial degeneration or necrosis. In addition, urinary OPN and NGAL, when used with sCr and BUN, increased the ability to detect renal tubular epithelial degeneration or necrosis. NGAL and OPN had comparable or improved performance relative to Kim-1, clusterin, albumin, total protein, and beta-2 microglobulin. Given these data, both urinary OPN and NGAL are appropriate for use with current methods for assessing nephrotoxicity to identify and monitor DIKI in regulatory toxicology studies in rats. These data also support exploratory use of urinary OPN and NGAL in safety monitoring strategies of early clinical trials to aid in the assurance of patient safety.